The Evolution of the Ombudsman Institution: An Academic Perspective - Petrisor , Maria Florentina (Acta Universitatis Danubius. Juridica, 2025)
This article explores the historical development, institutional evolution, and contemporary relevance of the Ombudsman institution, focusing on its role as a mediator between citizens and public authorities. Originating from early administrative practices and formally institutionalized in Sweden, the Ombudsman has become a key mechanism for safeguarding individual rights and promoting governmental accountability. The study examines the expansion of the Ombudsman model globally, with particular emphasis on its emergence in post-communist states as part of democratic transitions. The article also addresses the absence and potential role of such an institution in authoritarian regimes, with a specific focus on North Korea. Through analysis of political, legal, and social contexts, it argues that the establishment of an independent Ombudsman requires systemic political transformation, highlighting the challenges and prospects of implementing this institution in repressive environments. The work concludes by reflecting on the Ombudsman’s enduring significance in fostering transparency, justice, and citizen empowerment in diverse governance frameworks.